1982
DOI: 10.1111/j.1432-1033.1982.tb19786.x
|View full text |Cite
|
Sign up to set email alerts
|

The Glucose/Glucose‐6‐Phosphate Cycle in the Periportal and Perivenous Zone of Rat Liver

Abstract: Periportal and perivenous hepatocytes contain different activities ( V ) of antagonistic key enzymes such as glucokinase and glucose-6-phosphatase. In order to get an insight into the metabolism of the periportal and perivenous area the flux rates (v) of the glucose/glucose-6-phosphate cycle were calculated on the basis of the Michaelis-Menten equation using the measured zonal concentrations of glucose and glucose 6-phosphate, the zonal activities of glucokinase and glucose-6-phosphatase previously reported an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 89 publications
(41 citation statements)
references
References 57 publications
3
38
0
Order By: Relevance
“…By allowing 45 min of narcosis before taking blood samples [37], the handling stress had faded as indicated by two observations. (a) Peripheral adrenaline and noradrenaline levels had returned to low normal values [35] of 0.7 nM and 1.0 nM, respectively, after 35 min of narcosis (data not shown).…”
Section: I2/lc'thdolog~mentioning
confidence: 99%
“…By allowing 45 min of narcosis before taking blood samples [37], the handling stress had faded as indicated by two observations. (a) Peripheral adrenaline and noradrenaline levels had returned to low normal values [35] of 0.7 nM and 1.0 nM, respectively, after 35 min of narcosis (data not shown).…”
Section: I2/lc'thdolog~mentioning
confidence: 99%
“…Hepatocytes from the periportal zone of the liver have different enzyme activities from the perivenous zone. 42 It has been shown that the periportal zone has relatively high gluconeogenesis rate since the zone is rich in enzyme activities such as glu cose-6-phosphatase, fructose 1,6 bisphosphatase and phosphoenolpyruvate carboxykinase, while the peri venous zone is rich in glycolytic enzyme activities such as pyruvate kinase and glucokinase. During the absorptive phase, the perivenous cells take up glucose from the blood and convert it into glycogen and lac tate.…”
Section: A Distributed Model Of Carbohydrate Transport and Metabolismmentioning
confidence: 99%
“…The perivenous cells are rich in the glucose-utilizing enzymes glucokinase [7,13,141 and pyruvate kinase L [9,15]. Evidence that the periportal cells are predominantly gluconeogenic and the perivenous cells glycolytic comes from studies in vivo and in vitro: zonal flux differences were calculated from enzyme and metabolite distributions measured in vivo [16]. They were observed in periportal-like and perivenous-like hepatocytes in Correspondence to K. Jungermann [18,191.…”
Section: Modulation By Oxygen Of the Glucagon-dependent Activation Ofmentioning
confidence: 99%